Association of CYP1A1 gene polymorphism with breast cancer incidence - Hayder Ayyal Mutar (International Journal of Research in Pharmaceutical Sciences, 2023)
This study was aimed to investigate the molecular detection of the CYP1A1 gene polymorphism and its role in breast cancer enhancement. Additionally, understanding some of the environmental factors and their relationship to the occurrence of breast cancer was proposed for this study. Blood samples were collected from 50 women at ages between 21-71 years old, that suffered from breast cancer and 50 healthy women who are considered as a control group. The samples were placed in EDTA-based tubes. Then, the samples were kept frozen at -20 ̊C for later DNA extraction and polymerase chain reaction (PCR) laboratory procedures. The results of the mutation analyses of the CYP1A1 gene for the cancer and the healthy groups revealed that the occurrence frequencies of the homozygous wild type isoleucine/isoleucine were 52% and 26% respectively. While they were 42% and 60% respectively for the homozygous mutant Val/Val. Moreover, the heterozygous mutant Val/Ile type showed presence at 6% and 14% respectively. The statistical analyses confirmed that the incidence of the breast cancer could increase with genetic trait of the homozygous mutant Val/Val in a difference rate of 1.4 and confidence interval at 3.337-0.587. The findings of this study also declared that the women who carried the heterozygous mutant Val/Ile and their menstrual cycle started at the ages between 14-17 years old had 4 times of the risk factor of developing breast cancer. The study also revealed that there were no significant differences between the women who had breast cancer if they had early or late menopause. Finally, the study results showed that there was 3 times risk factor of developing breast cancer in uneducated women when linked to the genotypic trait Val/Ile in a difference rate of 3.2 and confidence interval of 40.057-0.265. It has been concluded that the risk factor of breast cancer was increased in the uneducated women in the presence of the Val/Ile genotype. This could be reasoned to the lifestyle of exposing to chemicals, paints, smoking, and many environmental carcinogens.